Kesalehan dan Politik: Islam Indonesia - Azyumardi Azra (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
Thomas B. Pepinsky, R. William Liddle, and Saiful Mujani. 2018. Piety and Public Opinion: Understanding Indonesian Islam. Oxford: Oxford University PressSaiful Mujani, R. William Liddl, and Kuskridho Ambardi. 2018. Voting Behavior in Indonesia since Democratization: Critical Democrats. Cambridge: Cambridge University Press.This article aims to review two books written by four foremost scholars in the field of political science. In the context of understanding Islam and the culture of democracy, these two books can answer questions that are often discussed, that is the relationship between religious piety and political behavior in Indonesia. Quantitatively, 99.7% of total Muslims in Indonesia state that religion is an important element in their lives. However, in terms of political preferences, this fact does not have implications for the votes obtained by Islamic-based political parties, especially in the post-Soeharto elections. They, instead of carrying out their own candidates, tend to be supporters in the presidential election and local leaders elections. To figure out this puzzle, these books are very pivotal works to understand the relationship between Islamic piety and politics. Both of these books show that there has been an increase in the level of piety of the Indonesian Muslims in the past two or three decades. However, creating piety does not affect their political behavior - specifically their voting behavior in elections.